PENGALAMAN KOMUNIKASI ANAK TANPA PERAN ORANG TUA DALAM PEMBENTUKAN KONSEP DIRI DI PANTI ASUHAN - Putri Pangestu, Tiara; Luqman, Yanuar; Manalu, S. Rouli (Interaksi Online, 2024)
Indonesia is the sixth most orphaned country in the world. Not only orphans, many children grow up without parents due to divorce, economic deprivation, and neglect by their biological fathers and mothers. Living without the role of parents makes children experience many difficulties in forming a positive self-concept due to the lack of communication and direction from parents as the first group of children. Many children without the role of parents end up living in orphanages in order to continue their lives properly. This study aims to understand the communication experience of children without the role of parents in the formation of self-concept in orphanages. This research was conducted using the Interpretative Phenomenological Analysis (IPA) method with in-depth interview techniques to five children without the role of parents who are foster children in orphanages. This research draws on Mead's theory of symbolic interactionism self-concept. The results of this study show that children without the role of parents can still have a positive self-concept as they grow by establishing good interpersonal communication with caregivers in orphanages. The two-way communication model and the effectiveness of interpersonal communication between the two parties can make children still feel valuable and worthy of a bright future even without the role of parents. The child's self-image is also formed from the positive view of the environment towards the child. Even so, there are still communication barriers that arise in orphanages. The most common barriers experienced are semantic barriers in the form of language differences and psychosocial barriers resulting from past trauma.